Analysis of Productivity and Labor Requirements of Palm Oil (Elaeis guineensis Jacq.) Harvesting at Afdeling 4 in PT. Alam Jaya Persada - Wartomo; Novi Indah Lestari; Sri Ngapiyatun; Humairo Aziza; Rusli Anwar; Puspita (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2024)
In facing increasingly competitive competition, every company needs quality human resources (HR) who have high competence. The challenges that are often faced by every company are the demand for production, which is quite high, and the quality of the products produced. Based on this, human resource management is needed according to the needs of the company. This study aims to determine the characteristics of harvesting employees, the productivity of harvesting employees, and the number of effective oil palm harvesting labor requirements in Afdeling 4 at PT. Alam Jaya Persada. This study uses two data sources, namely primary data consisting of interviews, direct observation, and documentation, as well as secondary data consisting of company documents and literature related to research activities. Respondents in this study amounted to 22 harvest employees who were determined using saturated sampling techniques. Research data collection was carried out through direct observation, interviews, and collecting all documents related to research. Data analysis used in managing research data is descriptive analysis. Based on the characteristics of harvest employees, 22 people are all male with a percentage of 100%; the average education of employees, namely elementary school (SD), is 10 employees with a percentage of 45%; based on an average age of 31–40 years, namely 9 employees with a percentage of 41%; and based on the average length of work of 1-2 years, namely 11 employees with a percentage of 50%. The results showed that of the 22 harvesting employees of Afdeling 4, the average productivity of harvesting employees was 163 beds/HK, and the basis set by the company was 120 beds/HK. This shows that Afdeling 4 employees can be said to be very productive. The calculation of the need for effective employees in Afdeling 4 is 18 harvesting employees with an area of 728 ha, but the number of employees in the field is 22 or has exceeded the labor requirements for the area of the land.